Solar drying of guavas, papayas and apples - Hawlader, Mohammad Nurul Alam; Lee, Hwee Peng (IIUM Press, 2011)
This paper includes the results of a study carried out to determine the drying characteristics of three agricultural fruit products. The products used in this analysis were apples, guavas and papayas. The drying characteristics of the three products were investigated under different operating conditions by varying now velocities and the thickness of the specimens. An experimental solar dryer was built to conduct tests on different samples. Tests were carried under both natural and forced convection conditions. Different meteorological conditions were considered in the experiments. A analytical model. based on Fick's second law of diffusion. was used to determine the effective diffusion coefficients of the three products. The diffusion coefficients were obtained from the slope of in (w/wo) against t/L2. It was found that the diffusivities of apples, guavas and papayas range between 5.74xI0-12 and 8.6IxI0-IO 1112/s. It was also observed that shrinkage occurred in the above three specimens during drying. This effect was taken into account and a correction factor for thickness, L, was introduced.